Analisis Kebutuhan Jumlah Petugas Koding BPJS dengan Metode Analisis Beban Kerja Kesehatan di Rumah Sakit Umum Haji Surabaya - Diyan Juli Eka Lestari; Djazully Chalidyanto; Ririn Rakhmawati (Media Gizi Kesmas, 2024)
Background: The number of inpatient BPJS claim files is 13,427 and outpatient claims are 139,027. This means that the average number of outpatient claim files that must be processed is 446 per day and 43 claim files per day for inpatient care. Meanwhile, the number of coding officers available is 6 people, consisting of 3 outpatient coding officers and 3 inpatient coding officers. The large number of claim files that each inpatient and outpatient coding officer has to work on causes the coding officer to feel the workload is heavy. The heavy workload on coding officers will cause fatigue among coding officers which will result in errors in the claims process and impact on the return of 7,402 claim files or 4.85% of the total 152,454 claim files. The return of these claim files caused the target set by the Haji Surabaya Regional General Hospital for claim files to be eligible for payment of 100.00% not to be achieved. Objectives: To determine the need for the number of coding officers at the Haji Surabaya Regional General Hospital. Methods: This research uses secondary data obtained from the coordination controller installation and casemix unit. The data was then analyzed based on the Health Workload Analysis method and then presented descriptively in the form of tables and explanations Results: The average activity time for outpatient coding officers is 1 to 3 minutes per activity, while for inpatient coding officers 2 to 8 minutes per activity. The standard workload for outpatient coding officers is 117,180 for 3 types of activities and 58,590 for 1 type of activity, while inpatient coding officers are 14,647 for 3 types of activities, 23,436 for 2 types of activities and 58,590 for one type of activity. The standard for supporting duties for inpatient and outpatient coding officers is 1.072. Based on the average activity time, workload standards, and supporting task standards, the calculation results are obtained The number of coding officers needed is 6 people for outpatient care and 3 people for inpatient care. Conclusions: The number of coding officers needed for outpatient care is 6 people, which is not in accordance with the number currently available, so it is necessary to increase the number of coding officers by 3 people, while for inpatient coding officers, the number needed of 3 people is in accordance with the number available so it is not needed. addition or reduction in the number of coding officers.